Sistem Pakar Dalam Mendiagnosa Penyakit Tubercolosis dengan mengimplementasikan Metode Case Based Reasoning - Aris Wijayanti; Fatimah Nur Arifah; Desfita Eka Putri; Muhammad Dwi Satriyanto; Sulfikar Sallu (Journal of Computer System and Informatics (JoSYC), 2023)
Health is one of the most valuable parts of human life. So healthy is the goal of every human being. Many things cause the decline in human health, such as hereditary genes, sensitive immunity and exposure to viruses or bacteria. One of the diseases caused by bacteria is tuberculosis (TB). Tuberculosis is a disease caused by exposure to a bacterium called Mycobacterium tuberculosis. There are two types of tuberculosis, namely pulmonary tuberculosis and extra pulmonary tuberculosis. Pulmonary tuberculosis can be defined as a disease that attacks the lungs and affects the lung parenchyma [4]. It's just that this type of disease does not attack other organs. While extrapulmonary tuberculosis is a tuberculosis disease in which this type of disease can attack other related organs such as the hilum, pleura and various other organs. the lack of funds for health checks makes it too late for many people to get treatment. Therefore, the development of technology should be utilized in handling this problem. One of the technologies that can be used in dealing with these problems is to use an expert system. An expert system is a system that is developed using the development of the knowledge that is owned by many experts and is used as a reference in developing the technology. In using an expert system, a method is needed that can help solve existing problems, therefore in this study the method used is the Case-Based Reasoning (CBR) method. The Case-Based Reasoning (CBR) method is the most suitable method for use in this study because the main function of this method is to diagnose disease. Based on the results of the calculation process using the Case-Based Reasoning method for each type of TB disease, the results obtained are for pulmonary tuberculosis to obtain a value of 85%, while for tuberculosis with extra pulmonary tuberculosis it is 62%. So based on the results obtained in this study it was determined that the sample was diagnosed with pulmonary tuberculosis. With a similarity of 85%.